Six Degrees-of-Freedom Direct-Driven Nanopositioning Stage Using Crab-Leg Flexures - Kang, Sunghoon; Lee, Moon Gu; Choi, Young Man (IEEE/ASME Transactions on Mechatronics, 2020)
This article presents a novel six degrees-of-freedom nanopositioning stage having a low-profile shape. The six degrees-of-freedom motion is achieved in a parallel configuration comprising four crab-leg flexure guide mechanisms and eight electromagnetic actuators. The crab-leg flexure can be engineered to exhibit similar stiffness levels in all the directions. The noncontact direct-drive nature of the electromagnetic actuators and the symmetric layout simplify the kinematics and result in considerably low coupling between the motion axes. For design optimization, we derived an analytical model that described the static and dynamic performances of the proposed stage using the matrix method. Then, we fabricated the stage with a stroke of 0.5 mm in the translational directions and 5 mrad in the rotational directions. The stage measured 250 mm × 250 mm × 57.4 mm. In an open-loop operation, the six-axis motions exhibited linear and repeatable performances. The maximum parasitic error was less than 1.8% of full scale. The tracking errors for the closed-loop control of the 5 Hz sinusoidal trajectory were less than 222 nm and 4.2 μrad. The temperature elevation was 5.8 °C after 3 h using half of the entire power consumption. The stage was utilized for developing an autofocusing system in dynamic scanning using an optical microscope.
Keywords: Electromagnetic actuators; Nano-positioning stages; Parallel configuration; Rotational directions; Sinusoidal trajectories; Six degrees of freedom; Static and dynamic performance; Translational directions; Actuators; compliant mechanism; design optimization; motion control; nanopositioning